Profile of serum calcium, inorganic phosphorus, total protein, albumin and globulin in superovulated cattle - AGRAWAL, PRANAY; MAURYA, S N (The Indian Journal of Animal Reproduction, 2023)
Thirteen, gynaecologically nonnal, Sahiwal cows were treated with 50 mg FSH-E in eight divided doses.The donors were classified as good (>3 CL), poor (3 CL) or non(< 3 CL) responders. The blood serum levels ofcalcium, inorganic phosphorus, total protein, albumin and globulin were estimated in all cows on day of PGFp.treatment, day of superovulatory estrus and day of embryo collection. The serum concentrations of all the aboveparameters were lower in non responding than poor and good responding donor cows.
Keywords: Superovulation; cattle; calcium; phosphorus; albumin; globulin; total protein